Avaliação da susceptibilidade à fragilização por hidrogênio in situ em microconstituintes por meio de nanoindentação instrumentada - Leal, José Eduardo (2021)
This work evaluated the hydrogen embrittlement susceptibility (HES) by means of electrochemical nanoindentation. Three steels (AISI 4130M, AISI 4137M and AISI 4140) and two Ni-alloys (UNS N07718 (Inconel 718®) and CMSX-4) were evaluated. Nanoindentation tests with different loading rates were performed under in situ hydrogen (H) charging. Hydrogen charging was carried out using cathodic polarization of samples immersed in a NaCl 3.5 % aqueous solution. For UNS N07718 tests were performed on grains with two different crystallographic orientations. In turn, for the AISI 4130M steel and CMSX-4 alloy, continuous multicycle (CMC) indentation type was carried out. Exclusively for the CMSX-4 alloy, incremental step loading indentations (N-ISL) were performed. It was possible to conclude that the HES evaluation by electrochemical nanoindentation is influenced by the proper selection of the loading rate. The N-ISL profile was efficient for HES evaluation since it favors the H accumulation under the indenter tip, enhancing its effect. Under the investigated experimental conditions all materials are susceptible to hydrogen embrittlement since the following H effects were observed: i) the H permeation increased the AISI 4137M and AISI 4140 steels nanohardness (HIT) in 9.8 % and 15.3 %, respectively, for a 5 mN/min loading rate. ii) The CMC indentation evidenced the H effect on the AISI 4130M steel HIT. In all loading cycles the HIT was reduced between 7 % and 10 % HIT. iii) For the UNS N07718, without the grain identification, the permeation of H under constant potential increased the HIT values in 16.2 % and 15.3 % for 15 mN/min and 480 mN/min loading rates, respectively. iv) Under galvanostatic H permeation and using a 5 mN/min loading rate the UNS N07718 presented a HIT reduction of 8.7 % and 3.6 % for grains with the lowest and the highest Schmid factor, respectively; v) using N-ISL indentations, it was observed that the H reduced the HIT values in 37 %.